Transition Flight between the Autonomous Flight Airspace and Automated Airspace - Magister, Tone (Promet - Traffic&Transportation, 2008)
The paper proposes a novel Autonomous Flight Airspaceconcept as a bridge between pure innovation and integration ofthe existing and envisioned highly automated ATM concepts,methodologies, metrics, and procedures. Novel technologies,operations, and procedures will lead to air traffic flows withnovel properties which together with adapted geometry and organizationof airspace will define the complexities of air trafficsituations in the Autonomous Flight Airspace and in its neighbourhood.The problem of transition flights to and from theAutonomous Flight Airspace is addressed from the complexityof in-flight traffic situations and consequent increase in conflictsbetween aircraft in the area perspective. Those are thedriving criteria for the positioning of transition layers betweenthe Autonomous Flight Airspace and the controlled airspace,their organization, and management of traffic flows in bothzones adjacent to the boundary between them as well.